Dampak Film Para Pencari Tuhan Jilid X Terhadap Religiusitas Remaja - Robby Aditya Putra (Jurnal Dakwah dan Komunikasi, 2018)
This research proved that da’wa materials presented through serial religious soap opera, with good composition, can form da’wa materials which affected teenage religiosity. This research was in line with John C. Lyden in Film as Religion (2003), and Rachel Dwyer in Filming the Gods, Religion and India Cinema (2006), they contended that proselytizing activities with the media, especially film, had stronger effect to audiences, and became easier to understand than that of spoken orally.But it is present as the antithetical research of L. Rowell Huesmann in The Impact of Electronic Media Violence: The Scientific Theory and Research (2007). This research employed qualitative method by using impact analysis technique. The data gained from library study, observation, interviews, objectivity, and documentations.